Temperature Dependence of the Surface- and Buffer-Induced Current Collapse in GaN High-Electron Mobility Transistors on Si Substrate - Zhang, Chuan; Wang, Maojun; Xie, Bing; Wen, Cheng P.; Wang, Jinyan; Hao, Yilong; Wu, Wengang; Chen, Kevin J.; Shen, Bo (IEEE TRANSACTIONS ON ELECTRON DEVICES, 2015)
The temperature dependence of current collapse (CC) in AlGaN/GaN high-electron mobility transistors on silicon substrate is studied in this paper. Devices without and with Si3N4 passivation are used to investigate the behavior of surface- and buffer-induced CC, respectively. It is found that the degree of surface-induced CC in unpassivated devices has a weak temperature dependence, which is induced by the cancelling out between enhanced carrier injection based on surface hopping and enhanced emission when the temperature is increased. On the other hand, the degree of buffer-induced CC in the Si3N4 passivated devices is reduced at higher temperature since the energy of hot electrons is reduced due to the phonon scattering and the trapping of hot electrons in the buffer is mitigated. Temperature-dependent transient measurement is also carried out to investigate the recovery process for these two type of CC. Two types of trap levels are identified in the unpassivated and Si3N4 passivated devices, respectively. The trap level E1 with an activation energy of 0.08 eV is supposed to be related to the surface trapping, while E2 with an activation energy of 0.22 eV is located in the buffer layer.